2003
DOI: 10.1080/1042819031000083037
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance Between Apoptosis and Telomerase Activity in Myelodysplastic Syndromes: Possible Role in Ineffective Hemopoiesis

Abstract: The myelodysplastic syndromes (MDS) are a group of disorders characterized by peripheral pancytopenia despite normo- or hyper-cellular bone marrow. This is thought to be due to apoptosis of hematopoietic bone marrow cells, resulting in ineffective hematopoiesis. The heterogeneous nuclear ribonucleoprotein (hnRNP) B1 is involved in pre-mRNA processing and binds to telomeric cDNA repeats. The hnRNP B1 is a marker for early cancer. The aim of our study was to clarify the relationships between prognosis and apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 31 publications
2
12
1
Order By: Relevance
“…In the present study we tested both hTERT expression and telomerase activity in the same group of MDS patients and found that telomerase activity as well as hTERT expression were higher in MDS patients and AML/MDS than in controls, the increase being more pronounced in patients with more severe disease (RCMD, RAEB, AML), in agreement with the results reported by Oshima et al 36 However, the telomerase activity appeared to be Telomerae activities and the expression levels of hTERT mRNA in both controls and MDS patients were well correlated. The Spearman rank correlation was 0.524 and p = 0.0486. c-Myc, mad1 and p53 expression.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the present study we tested both hTERT expression and telomerase activity in the same group of MDS patients and found that telomerase activity as well as hTERT expression were higher in MDS patients and AML/MDS than in controls, the increase being more pronounced in patients with more severe disease (RCMD, RAEB, AML), in agreement with the results reported by Oshima et al 36 However, the telomerase activity appeared to be Telomerae activities and the expression levels of hTERT mRNA in both controls and MDS patients were well correlated. The Spearman rank correlation was 0.524 and p = 0.0486. c-Myc, mad1 and p53 expression.…”
Section: Discussionsupporting
confidence: 81%
“…On the contrary Campbell et al 35 recently reported that hTERT is downregulated in the hematopoietic stem cells of patients with chronic myeloid leukaemia. Oshima K, et al 36 found that telomerase activity is higher in AML/MDS than in MDS and controls, whereas opposite results were reported by other authors 16 that did not find significant differences in telomerase activity in bone marrow of MDS patients compared to controls. It must be remarked that in literature data telomerase activity and hTERT expression were independently investigated by different groups in MDS patients, and this may account for some discrepancies in reported results.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…4 In fact, approximately two-thirds of patients present with lower risk disease characterized by hypercellular marrows with increased rates of apoptosis in the progenitor and differentiated cell compartments in the marrow. [5][6][7][8] Ineffective hematopoiesis arising from abortive maturation leads to peripheral cytopenias. Higher grade or more advanced disease categories are associated with a significant risk of leukemia transformation, with a corresponding lower apoptotic index and higher percentage of marrow blasts.…”
Section: Introductionmentioning
confidence: 99%
“…4 Approximately two thirds of patients present with lower-risk disease (Low and Int-1 IPSS scores) characterized by increased rates of apoptosis in the progenitor and differentiated cell compartments in the marrow. [5][6][7][8] High intramedullary apoptosis leads to ineffective hematopoiesis and peripheral cytopenias. Higher grade or more advanced disease categories (Int-2 and High IPSS scores) are associated with a significant risk of leukemia transformation with a corresponding lower apoptotic index and higher percentage of marrow blasts.…”
Section: Introductionmentioning
confidence: 99%